2019
DOI: 10.3897/zookeys.871.36880
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of freshwater Copepoda (Crustacea, Hexanauplia) from continental Ecuador and the Galapagos Archipelago

Abstract: An annotated checklist of the free-living freshwater Copepoda recorded in different regions in Ecuador (including the Amazon, the Andes, the coastal region, and the Galapagos Islands) is here provided. We revised all published records, critically evaluated the validity of each taxon and provided short taxonomic and biogeographical remarks for each one. A total of 27 taxa have been reported, including species and records at the generic level only. The species and taxa identified only up to the generic level bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Verification of this identification is still needed (Corgosinho et al, 2019) and a formal description is still awaited (E.N.d.S.S., personal communication). The diaptomid copepod species from El Junco Lake appears to be the only diaptomid species known to occur in the entire archipelago (Peck, 1994;Corgosinho et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Verification of this identification is still needed (Corgosinho et al, 2019) and a formal description is still awaited (E.N.d.S.S., personal communication). The diaptomid copepod species from El Junco Lake appears to be the only diaptomid species known to occur in the entire archipelago (Peck, 1994;Corgosinho et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Verification of this identification is still needed (Corgosinho et al, 2019) and a formal description is still awaited (E.N.d.S.S., personal communication). The diaptomid copepod species from El Junco Lake appears to be the only diaptomid species known to occur in the entire archipelago (Peck, 1994;Corgosinho et al, 2019). This diaptomid copepod species was not found in any of the collections made after 2006; thus, its disappearance is synchronous with the introduction and eradication of the Nile tilapia in the lake, and plausibly linked to it (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, no endemic freshwater zooplankters besides M. galapagoensis have been found in the archipelago, but all freshwater ecosystems (temporary or permanent) have not been thoroughly studied, particularly for zooplankton composition. So far, we know only the report on rotifers of Segers (1991) , a bachelor thesis Obando (2009) , and the checklists of cladocerans by Lopez et al (2018a) , rotifers by López et al (2020) and copepods ( Peck, 1994 ; Corgosinho et al, 2019 ). We consider doubtful the records of marine copepods ( Acrocalanus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The first mention of the copepod was by Steinitz-Kannan (1979) , who noted its resemblance with Notodiaptomus amazonicus and observed that in July 1966, July 1977, and December 1978, there was a disproportionate large number of adults (up to 80% of the sampled population) compared to nauplii larvae and copepodites, presumably resulting from a slow turnover of the population. According to Corgosinho et al (2019) , this copepod population is the only calanoid species in inland waters of the archipelago and needs taxonomic verification. Recently, Dr. Miriam Steinitz-Kannan brought the existence of these copepods to the attention of Dr. Carlos López who examined the specimens from the 2004 collection and recruited Dr. Manuel Elías-Gutiérrez and Dr. Eduardo Suárez-Morales to aid with the taxonomic identification.…”
Section: Introductionmentioning
confidence: 99%